An investigation into the relationship between music preference, personality and psychological wellbeing - Sigg, Nicola (Auckland University of Technology, 2009)
There is a large amount of research demonstrating a correlation between the effect of music on young people, especially in regards to suicidal ideations, but only a handful of studies examining why individuals subscribe to the music genres they do. Of those studies that have touched on this subject none have looked at multiple variables, specifically social identity theory, personality, and psychological wellbeing, and none have looked at these variables in regards to a New Zealand population. Thus, the aim of this research was to examine the relationship between music preference and each of these three variables amongst a New Zealand university population. It was reasoned that if a correlation was found it may benefit psychologists working with youth, specifically providing a greater understanding of these clients and aid in how therapy is conducted. The research was performed using six quantitative surveys: the Depression, Anxiety, and Stress Scale (DASS-21), the Rosenberg Self-Esteem scale (RSES), the Self-Attributes questionnaire (SAQ), the Self-Liking/Self-Competency Scale – Revised (SL/SC-R), the Ten-Item Personality Inventory (TIPI), and a music preference survey, the STOMP-M, which assessed the type of music the participants were inclined to listen to. The participants were selected using convenience sampling; and consisted of 314 first year university students studying at Auckland University of Technology. The results of this study indicated no relationship between music preference, as an aspect of social identity, and self-esteem. A relationship was found between some music preference factors and some personality traits. A correlation was also observed between some music preference factors and some aspects of psychological wellbeing.
Keywords: Music preference; Personality; Social identity theory; Self esteem; Depression; Anxiety; Stress